Antimicrobial nanocomposites: Cellulose fibers loaded with silver nanoparticles in health products - Araújo, Tiago Lopes de; Carneiro, Camila Nunes; Pessoa, Pedro Henrique; Borges, Augusto Guilherme Feitosa Cacho; Luna, Pâmela Barcelar Ferreira Gomes da Silva de; Souza, Karina Carvalho de (Seven Editora, 2023)
Polymeric nanocomposites based on cellulose fibers, mainly cotton, and loaded with silver nanoparticles have been used mainly in health products (such as endotracheal tubes, bandages, medical dressings, mesh, catheters and filters) thanks to the fact that these nanoparticles have broad-spectrum antiseptic properties. Based on the analysis of scientific publications, this work aims to investigate how these nanocomposites have been prepared and characterized in general, with regard to the characteristics and properties of silver nanoparticles and their synthesis by chemical, photochemical, physical and biological methods and how they are impregnated in cellulosic fibers. Specific considerations will also be made regarding the antimicrobial mechanism of nanostructured silver and its toxicity to humans. DOI:https://doi.org/10.56238/globalhealthprespesc-065